RELATIONSHIP BETWEEN POWER CAPABILITY LEG MUSCLESHOOTING WITH FOOTBALL ON STUDENT JUNIOR CITY STATE 17 PEKANBARU - Arif Lukman Hakim Lukman Hakim; Ramadi '; Yuherdi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: In the SMP 17 Pekanbaru, especially male students of class VIII, shooting less than satisfactory results, it appears, among others, the shooting of the student is not quite right on target, difficult to be controlled by a team of friends, often bounced the ball low and so forth. Mistakes made by students after the initial observation was caused by the student has not mastered the correct shooting techniques by students. Students are just trying to win the game regardless of how doing the right shooting so often happens one operand. The problem in this research is: Is there a relationship leg muscle power with the ability to shoot at students of SMP Negeri 17 Pekanbaru?The population in this study were a total of 14 players. The sample in this study were students who take extra in SMP 17 Pekanbaru as many as 14 students (100%). Sampling used purposive sample technique.The results showed that the frequency distribution of the results of 14 samples, was at most 6 samples = 42.9% gain value Jump MD with a range of values ​​from 39.3 to 42.5. The results of the frequency distribution, turns at most 4 samples = 28.57% with a range from 109.37 to 117.39 value. To relation variable X with variable Y obtained rhitung = 0.646> rtabel = 0.532, then there is a relationship between variables X with variable Y. Conclusion accepted hypothesis at significance level α = 0:05 in other words there is a significant relationship between leg muscle power with the results of shooting ability the students who take extra in SMP 17 Pekanbaru. Keywords: Muscle Power Limbs,Shooting Capability